Compartilhamento de informações e conhecimentos na comunidade virtual do SIGAA/UFPB - Gerbasi, Noadya Tamillys Oliveira Duarte (2017)
The sharing of information and knowledge is known as a human behavior, which is made possible by means of the dialogue among the individuals, in their environments of coexistence. Within organizations, this practice allows the synergy of information and the creation of new knowledge, resulting in innovation and improvements for the development of organizational processes. In this scenario, the information and communication technologies are considered as virtual environments that can subsidize the sharing among the individuals and result in new possibilities of coexistence in the organizations. Considering that this practice involves a set of intervening aspects - facilitators or inhibitors -, especially when mediated in virtual environments, it is analyzed the information and knowledge sharing in the virtual community of SIGAA, among the agents of the Federal University of Paraíba. Methodologically, the research is configured as a case study of the descriptive type, whose corpus is constituted by the virtual community environment and the people management agents. For data collection, it is used the form instruments, field diary, and questionnaire. For the analysis of the data, it is made an interpretation of the results from the quantitative and qualitative methods, through the techniques of content analysis and discourse analysis of the collective subject. And about the results concerning the resources available for the sharing in the virtual community, it is inferred that, although this environment has computational applications designed to subsidize the information and knowledge sharing, it must be available other types of resources that can help the practice of this behavior only at the tacit level, in order to promote the socialization of the individuals' experiences. With regard to the use of these resources for the sharing, it is observed that there was no continuity with the passage of time, resulting in a decrease in the frequency of users' participation. It is also noted that knowledge sharing practices did not present a high percentage in relation to the total of identified records, revealing that there is a preference for shares that involve the flows of formal informational (information). It is concluded that the intervening aspects of sharing among agents in this virtual environment, while involving facilitators, such as motivation to share and satisfaction of the individuals regarding the use of this mechanism, also present some inhibitors that need to be overcome, among them, the relationship among the agents, the culture and structure of the organization, and the understanding of these collaborators regarding the use of available resources. As recommendations, it is suggested initiatives that can involve, in an integrated way, the culture and structure of the organization, the agents and the resources of the virtual community.